2020
DOI: 10.1111/cyt.12899
|View full text |Cite
|
Sign up to set email alerts
|

Lesion‐targeted cytology to improve cytological sampling for atypical polypoid adenomyomas of the uterus: A case series and review of the literature

Abstract: Atypical polypoid adenomyomas (APAs) are uncommon mixed epithelial and mesenchymal tumours of the uterus. Patients present with abnormal uterine bleeding or hypermenorrhoea. Histologically, they are composed of atypical endometrioid glands that show architectural complexity or various cellular atypia embedded in a myomatous or fibromyomatous stroma that often contains squamous morules. 1-4 These findings might be confused as those corresponding to adenocarcinoma-infiltrating myometrium. However, APAs are more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Uterine adenomyoma is a gynecological disease with a high incidence among middle-aged multiparous women. It mainly refers to benign lesions of smooth muscle hyperplasia caused by diffuse invasion of endometrium into the myometrium, with dysmenorrhea, irregular menstruation, and increased menstrual volume as the main clinical manifestations [ 1 , 2 ]. Studies have shown that the incidence of uterine adenomyoma is related to sex hormone disorder, environment, cesarean section, induced abortion, and other operation-related factors, which can cause uterine enlargement, pelvic pain, and even infertility, which seriously affects female reproductive health and normal life [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Uterine adenomyoma is a gynecological disease with a high incidence among middle-aged multiparous women. It mainly refers to benign lesions of smooth muscle hyperplasia caused by diffuse invasion of endometrium into the myometrium, with dysmenorrhea, irregular menstruation, and increased menstrual volume as the main clinical manifestations [ 1 , 2 ]. Studies have shown that the incidence of uterine adenomyoma is related to sex hormone disorder, environment, cesarean section, induced abortion, and other operation-related factors, which can cause uterine enlargement, pelvic pain, and even infertility, which seriously affects female reproductive health and normal life [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%